Sexual harassment in university students of North of Lima: Acoso sexual en estudiantes universitarios de Lima Norte - Goyzueta , Ana Paula (2022)
Objectives: To determine the frequency of sexual harassment and harassing situations among students of a private university in North Lima. Materials and methods: Cross-sectional descriptive study conducted in 2019. The sample consisted of 355 students of both sexes from five academic schools. Results: Of 355 students with a mean age of 24.37 years (SD = 5.55; Range: 17 to 50), 93% (n = 330) were female, 62.3% (n = 221) belonging to the nursing school. Of the sample, 67.6% (n = 240) claimed to have received information about sexual harassment, 60% (n = 213) were victims of sexual harassment at some point in their life and 50.7% (n = 180) the stalker was male. Among the harassing situations, 24.5% (n = 87) were victims of physical contact or touching, 22.8% (n = 81) comments about some part of their body, 21.4% (n = 76) sexual comments and 17.5% (n = 62) through emails or harassing messages. The highest proportion of sexual harassment occurred in women (p = 0.003), in nursing school students (p = 0.020) and in those who received information about harassment (p <0.001). Conclusions: Sexual harassment is a very frequent problem in the university population, it mainly affects women nursing students. Physical contact or improper touching, comments on any body region and sexual comments were the main harassing situations. Keywords: Sexual harassment; Students; Students, Nursing; Peru (Source: MeSH, NLM).